Encapsidation of yeast killer double-stranded ribonucleic acids: dependence of M on L. - Bostian, K A (1980)
Virus-like particles containing either L or M double-stranded ribonucleic acid (dsRNA) were isolated from a killer toxin-producing strains of Saccharomyces cerevisiae (K+ R+). At least 95% of M- and 87% of L-dsRNA were recovered in virus-like particle-containing fractions. The major capsid polypeptides (ScV-P1) of both L and M virus-like particles were shown to be identical, and 95% of the cellular ScV-P1 was found in the virus-like particle-containing fractions. Since L-dsRNA encodes ScV-P1, provision of this protein for encapsidation of M-dsRNA defines at least one functional relationship between these dsRNA genomes and associates the L-dsRNA with the killer character. If encapsidation of M-dsRNA is essential for its replication or expression, then L-dsRNA plays an essential role in maintenance or expression of the killer phenotype. The relationship between the L- and M-dsRNA genomes would be analogous to that between a helper and a defective virus. The presence of only minor quantities or uncomplexed dsRNA and ScV-P1 suggests that their production is stringently coupled.